Effect of Oral versus Vaginal Administration of Estradiol and Dydrogesterone on the Proliferative and Secretory Transformation of Endometrium in Patients with Premature Ovarian Failure and Preparing for Assisted Reproductive Technology - Feng W; Nie L; Wang X; Yang F; Pan P; Deng X (Dove Medical Press, 2021)
Wenjuan Feng,1,2 Longyun Nie,3 Xiaoyu Wang,4 Fang Yang,1 Pan Pan,5 Xiaohui Deng1 1Center for Reproductive Medicine, Department of Obstetrics and Gynecology, Qilu Hospital, Cheeloo College of Medicine, Shandong University, Jinan, Shandong, 250012, People’s Republic of China; 2Department of Reproductive Medicine, Jinan Central Hospital, Cheeloo College of Medicine, Shandong University, Jinan, 250013, People’s Republic of China; 3Department of Obstetrics and Gynecology, Shenzhen University General Hospital, Shenzhen, Guangdong, 518055, People’s Republic of China; 4Department of Obstetrics and Gynecology, Peking Union Medical College Hospital, Beijing, 100730, People’s Republic of China; 5Department of Pathology, Jinan Central Hospital, Cheeloo College of Medicine, Shandong University, Jinan, 250013, People’s Republic of ChinaCorrespondence: Xiaohui Deng Tel +86 185 60082026Email dxh@sdu.edu.cnPurpose: This study aimed to assess the efficacy of vaginally versus orally administered estradiol (E2) and dydrogesterone (DG) on the proliferative and secretory transformation of endometrium in patients with premature ovarian failure (POF) and preparing for assisted reproductive technology.Methods: Twenty patients with POF who were awaiting oocyte donation were included in the study; they were randomly assigned to two groups to receive E2 and DG either orally or vaginally. Treatment efficacy was compared between the two groups regarding blood E2 concentrations, endometrial thickness, histology using hematoxylin and eosin staining, immunohistochemical analysis of ER expression, and PR and pinopodes morphology using scanning electron microscopy.Results: E2 concentrations differed significantly between oral and vaginal E2 and DG administration for 14 days (82.3 vs 1015.6 pg/mL; P < 0.001) and 21 days (85.0 vs 809.8 pg/mL; P < 0.001). Endometrial thickening was more pronounced in the vaginal treatment group, and also ER staining was stronger on days 14 and 21 in the vaginal treatment group. PR staining in the endometrium appeared more intense in the oral treatment group, which was, however, not significant. The abundance of developing pinopodes was higher in the vaginal treatment group (P = 0.04).Conclusion: Vaginal administration of E2 and DG is more effective than oral administration regarding proliferative and secretory transformation of the endometrium in POF patients and preparing for assisted reproductive technology.Keywords: micronized estradiol, vaginal administration, oral administration, pinopodes, premature ovarian failure